2014
DOI: 10.1007/s12221-014-0723-9
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical enhancement of UHMWPE fibers by coating with carbon nanoparticles

Abstract: Fiber-reinforced plastic (FRP) is composed of reinforced fibers and matrix resin, and has high specific strength and low-density materials. Because of the orientation of the fibers within them, FRPs are prone to buckling damage when under compression along the axial direction of the fiber, especially flexible organic ones. The compressive performance of FRP is largely dependent on fiber properties. the buckling load of FRP will increase with the increasing of fiber's. In this study, we developed a way to impro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Attempts will be made to enhance the resistance to fibrillation and buckling of AF and UHMWPE reinforcing fibers. For this purpose polymer coatings, produced by in situ polymerization from suitable monomers, such as pyrrole [169] are promising.…”
Section: Outlook and Future Trendsmentioning
confidence: 99%
“…Attempts will be made to enhance the resistance to fibrillation and buckling of AF and UHMWPE reinforcing fibers. For this purpose polymer coatings, produced by in situ polymerization from suitable monomers, such as pyrrole [169] are promising.…”
Section: Outlook and Future Trendsmentioning
confidence: 99%
“…They are used popularly to enhance the performance of biomaterials. A range of properties can be improved including osteoinductive properties [93], hydrophilicity [94], mechanical and biological properties [95,96], surface properties (e.g., surface free energy) [97], and biotribological properties [94]. Surface coating by adding materials on the top surface will be briefly reviewed in the next paragraph.…”
Section: Surface Coatingmentioning
confidence: 99%
“…Two groups of samples were tested at a sliding velocity of 0.05 m/s and a load of 5.23 N. The study reported a wear rate reduction of approximately 30% when the samples were surface coated with a thin layer (<20 nm) of DLCH. Nowadays, with the advancement of nanotechnology, nano-materials such as nano carbon tubes [96], have been used as a coating material to further improve the performance of the coating techniques.…”
Section: Surface Coatingmentioning
confidence: 99%
“…Researchers recognized the importance of understanding deformation modes (see Figure 6) other than axial tension that are occurring during an impact. Several researchers have investigated the single fiber transverse compression response of Kevlar fibers including Kawabata 98 , Singletary et al 99,100 and Cheng et al 87 and limited investigations on UHMWPE fibers 101 . The experimental results reported by these researchers indicate fibers exhibit nonlinear and inelastic response under large compressive strains.…”
Section: Fiber Length Scale Experimentsmentioning
confidence: 99%